Altered cerebral neurovascular coupling in medication-overuse headache: A study combining multi-modal resting-state fMRI with 3D PCASL - Li, Xin; Liu, Mengqi; Fan, Wenping; Xu, Huan; Chen, Zhiye (Frontiers in Neuroscience, 2023)
Abstract Aim: The brain structural and functional changes had been identified in medication-overuse headache (MOH) by using MRI. However, it was not clear whether the neurovascular dysfunction occurred in MOH, which could be elucidated by the neurovascular coupling (NVC) from the neuronal activity and cerebral blood flow viewpoints. This study is to investigate the potential altered NVC function of the brain in MOH by using resting state functional MRI (rs-fMRI) and 3D pseudo-continuous arterial spin labeling (3D PCASL) imaging techniques. Methods: Forty MOH patients and 32 normal controls(NCs) were recruited, and the rs-fMRI and 3D PCASL data were obtained from a 3.0T MR scanner. The standard preprocessing of rs-fMRI data was performed to generate regional homogeneity (ReHo), fractional amplitude of low-frequency fluctuation (fALFF) and degree centrality (DC) images. And the cerebral blood flow (CBF) images were obtained from the 3D PCASL sequence data. These functional maps were all be normalized into Montreal Neurological Institute (MNI) space and then NVC was defined as the Pearson correlation coefficients between the rs-fMRI maps (ReHo, fALFF and DC) and CBF maps. The statistical significance of the NVC in different brain regions were compared with Z test between MOH and NCs. Further correlation analysis was performed between the NVC and clinical variables for the brain regions with NVC dysfunction in MOH. Results: The NVC mainly presented negative correlation in MOH and NC. No significant difference was detected for the average NVC of the whole gray matter between the two groups. The regional brain regions with significantly decreased NVC located in left orbit part of superior frontal gyrus, bilateral gyrus rectus and olfactory cortex in MOH compared with NC (P < 0.05). The correlation analysis revealed that the DC of the brain regions with NVC dysfunction presented a significant negative correlation with disease duration (r = 0.323, P = 0.042), and DC-CBF connectivity showed a negative correlation with VAS score (r = -0.424, P = 0.035). Conclusions: The current study demonstrated that the cerebral NVC dysfunction presented in MOH patients, and the NVC technique would provide a new imaging biomarker in headache research.